Fungsi Rumah Adat dan Makna dalam Perspektif Kontemporer di Desa Sifalago Susua, Kabupaten Nias Selatan - Laia, Forman; Fitri, Hadiani; Hardiyansyah, Muhammad Ricky (Medan Resource Center, 2025)
This research aims to explore the meaning and function of traditional houses in Sifalago Susua Village, Susua District, South Nias Regency in the 21st century. The traditional houses in this region hold significant cultural and historical value and play a crucial role in the social and spiritual life of the community. Utilizing a qualitative approach and ethnographic methods, this study investigates community perceptions of changes and the sustainability of traditional house functions in the modern era. Data was collected through in-depth interviews with traditional leaders and villagers, participatory observation, and document analysis. The findings indicate that despite changes in various aspects of life due to modernization, traditional houses continue to serve important functions as symbols of cultural identity, sites for traditional rituals, and centers of social activities. The role of traditional houses as markers of social and economic status also remains relevant in the 21st century. Additionally, the research reveals that traditional houses possess strong spiritual significance, serving as a link between the present generation and their ancestors. However, challenges such as shifts in cultural values and global economic changes necessitate adaptive preservation efforts. In conclusion, traditional houses in Sifalago Susua Village remain a vital element in maintaining cultural identity and social bonds, despite the dynamics of changing times.